Novel Enzyme and Whole-Cell Biocatalysts - Sunna, Anwar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The concept of a circular economy relies on waste reduction, valorization, and recycling. Global trends for “green” synthesis of chemicals have positioned the field of enzyme technology and biocatalysis (multi-enzymes and whole-cells) as an alternative for the synthesis of more social- and environmentally-responsible bio-based chemicals. Recent advances in synthetic biology, computational tools, and metabolic engineering have supported the discovery of new enzymes and the rational design of whole-cell biocatalysts. In this book, we highlight these current advances in the field of biocatalysis, with special emphasis on novel enzymes and whole-cell biocatalysts for applications in several industrial biotechnological applications.